Building High Performance Teams through Collective Efficacy - Rashidi, Muhammad Zaki; Khan, Fouzia Naeem (JISR management and social sciences & economics, 2010)
Today’s organizations are changing their hierarchies due to the internal and external pressures and adapting innovative business processes; hence traditional functional pyramid and control is creating obstacles in handling sprouting issues and problems which require swift decision making. Teams are emerging as the basic unit of the organization to address this challenge and to enhance the productivity of the organizations by creating competitive edge achieved through teams’ flexibility and agile working style. Understanding the very nature of the teams and the natural cohesion of its members is essentially important for the organizations to build result oriented and high performance teams. Social cognitive theory underpins the concept of understanding of human behavior through perceived self efficacy; and its extension group efficacy is presently focused in research to understand the team dynamics specially, the individuals constituting these teams. The realization of self and group efficacy or collective efficacy, leads to comprehend the composition of forces working in formation of a cohesive group. Collective efficacy also has established its relationship with performance and various research studies concluded that collective efficacy is vitally playing a role in group performance. Hence to predict the performance of a group, it is necessarily required to evaluate the collective efficacy of the group. This research is an attempt to find the relationships of self efficacy, collective efficacy with the performance of a team by taking into account the team behavior. The study was conducted with teams working on projects and the data collected established the fact that team behavior and collective efficacy are the fundamental requirements to build high performance teams. The research also provides an insight to measure them in a team.